Antimicrobial Effect of Psidium guajava L. Leave Extract in Correlation with Biofilm Formation and Metallo-β-Lactamase Production in Multidrug Resistant Pseudomonas aeruginosa: Effect of plant extract on multi drug resistant bacteria - Thapa, Rabina; Raghubanshi, Bijendra Raj; Singh, Anjana (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
This study was aimed to determine antibacterial effect of P. guajava leave extracts and correlation of metallo-β-lactamase (MBL) production and biofilm formation with MDR P. aeruginosa isolated from different clinical samples. The study was carried out in the Kathmandu Institute of Science and Technology (KIST) medical college and teaching hospital and Central Department of Microbiology, Tribhuvan University, Kathmandu, Nepal. A total of 45 isolates of P. aeruginosa, isolated from different clinical samples were identified by standard microbiological techniques and antimicrobial susceptibility of the isolates was tested by Kirby-Bauer disk diffusion method on Muller Hinton agar as per CLSI guidelines. The ability to form biofilm was detected using the microtiter plate assay. MBL production was screened by Imipenem disk diffusion method and confirmed by Imipenem-EDTA combined disk method. P. guajava leave extracts were prepared using absolute methanol and hydroethanol solvent at different ratios. The antimicrobial activity of P. guajava leave extract against the pseudomonal isolates was determined by agar well diffusion method. Out of 45 isolates of P. aeruginosa, 30 (67%) were multidrug resistant (MDR) isolates, 30 (67%) were biofilm producers and 6 (13%) were metallo β lactamase (MBL) producers respectively. The methanol extract of fresh P. guajava leave (13mm) showed higher activity and least activity by 7:3 hydroethanol extract of dried P. guajava leave (6mm) toward the P. aeruginosa isolates. The methanol extract may be an alternative source for Pseudomonal infection treatment as antimicrobial resistance to available drugs which is increasing day by day. However, it should be standardized and tested in animal models before its application.